2016
DOI: 10.1080/08870446.2016.1218879
|View full text |Cite
|
Sign up to set email alerts
|

Impulse control disorders in Parkinson’s disease: Predominant role of psychological determinants

Abstract: Objectives: Impulse Control Disorders (ICDs) in Parkinson's disease (PD) have previously almost exclusively been considered to result from anti-parkinsonian medication. However, this biomedical perspective has failed to achieve a full understanding of the phenomenon and it is argued that a failure to consider psychological factors is a critical omission. Design: The present study examined the predictive relationship between ICDs in PD and a range of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 81 publications
1
22
0
4
Order By: Relevance
“…Interestingly, beyond biomedical factors (dopaminergic treatments), psychological determinants (negative coping strategy, illness identity, and psychological distress) have also been related to ICDs and related behaviors. 47 Similarly, we could speculate that the same factors would lead to the dissociation between objective and historical UDysRS scores only in clinical significant ICDs and related behaviors patients. Specific research including nondyskinetic PD is needed to address this question.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, beyond biomedical factors (dopaminergic treatments), psychological determinants (negative coping strategy, illness identity, and psychological distress) have also been related to ICDs and related behaviors. 47 Similarly, we could speculate that the same factors would lead to the dissociation between objective and historical UDysRS scores only in clinical significant ICDs and related behaviors patients. Specific research including nondyskinetic PD is needed to address this question.…”
Section: Discussionmentioning
confidence: 96%
“…We found similar objective UDysRS subscores among ICDs and related behaviors subgroups, indicating that additional factors modulate this relationship. Interestingly, beyond biomedical factors (dopaminergic treatments), psychological determinants (negative coping strategy, illness identity, and psychological distress) have also been related to ICDs and related behaviors . Similarly, we could speculate that the same factors would lead to the dissociation between objective and historical UDysRS scores only in clinical significant ICDs and related behaviors patients.…”
Section: Discussionmentioning
confidence: 97%
“…Efforts to identify the contribution of each factor for a specific ICD in PD showed that drug-induced mania, the use of DAs, early-onset of motor symptoms, severe depression and anxiety are risk factors for the development of gambling disorder 33 . Male sex, psychotic symptoms, dyskinesias and early onset of motor symptoms are associated with hypersexuality 11,17,36,39 . Female sex and obesity are correlated with binge eating 11,14 .…”
Section: Risk Factorsmentioning
confidence: 99%
“…Patients with PD and ICD tend to be described as shy with poor social skills, low self-esteem, beliefs based on a more negative perception of the disease, dysfunctional coping and paranoid ideation 39 .…”
Section: Neuropsychological Aspectsmentioning
confidence: 99%
See 1 more Smart Citation